Comparative Study of Malaria Prevalence among Travellers in Nigeria (West Africa) Using Slide Microscopy and a Rapid Diagnosis Test - T. V. Dougnon; H. S. Bankole; Y. M. G. Hounmanou; S. Echebiri; P. Atchade; J. Mohammed (Journal of Parasitology Research)
Malaria is a major disease in Africa and leads to various public health problems. A study was carried out at the Aviation Medical Clinic Laboratory, Murtala Mohammed Airport, Ikeja, Lagos State, Nigeria, in 2014. The work aimed to determine the prevalence of malaria among patients attending the laboratory. Blood samples were therefore collected from 51 patients and subjected to both blood smear microscopy and a rapid immunochromatographic diagnostic test (SD BIOLINE Malaria Ag) for detection of, respectively, malaria parasites and antigens. At the end of the study, 22% of the patients were detected positive by the microscopic examination while 9.8% were tested positive when using SD BIOLINE Malaria Ag. The outcomes of the study show a high prevalence of malaria at the airport. This represents a serious risk factor leading to a high likelihood of spread and occurrence of malaria in other countries including Western countries whereby the disease is nonendemic. It also pointed out that the blood smear microscopy seems to be better than Rapid Diagnosis Test (RDT) for malaria diagnosis.